Automated Model-based Test Case Generation Using Uml Activity Diagram: A Review - Rozi Nor Haizan , Nor; Md Abdul, Monim; Yusmadi Yah , Jusoh; Nur Ilyana Ismarau Tajuddin (Springer Nature Singapore Pte Ltd, 2024)
Volume: 782 (Page 109 - 121) 9th International Conference on IT Convergence and Security, ICITCS 2021Virtual, Online